Reptiles of the Atacama Region, northern Chile: localities, and representation in provinces, ecogeographic landscapes, vegetation formations and protected areas - Jorge Mella Ávila; Yery Marambio-Alfaro (Gayana, 2023)
We provide a checklist of reptiles distributed throughout the Atacama Region, northern Chile. Twenty- two species were found inhabiting this region, and their representation in provinces, ecogeographic landscapes, vegetation formations and protected areas were registered. We documented 204 localities for reptiles in the Atacama region. Of the three administrative provinces into which the Atacama Region is divided, Copiapó is the one with the highest richness of reptile species, with 19 species in total. The species with the highest number of recorded localities are Liolaemus nigromaculatus (n = 49 localities), Callopistes maculatus (n = 40), L. rosenmanni (n = 32), L. atacamensis (n = 31) and L. platei (n = 30). In contrast, the species with the fewest recorded localities are L. andinus, with only one locality, L. nigrocoeruleus, with two localities, L. zapallarensis (n = 3), L. robertoi and L. fuscus (n = 4). The species present in the largest number of ecogeographic landscapes (n = 7) was C. maculatus, while at the other end, L. fuscus, L. nigrocoeruleus, L. zapallarensis and Microlophus atacamensis were only found in one ecogeographic landscape. The reptile species present in the greatest variety of vegetation formations were L. platei and C. maculatus (recorded in six formations), while L. nigrocoeruleus, L. silvai and M. atacamensis were recorded in only one type of vegetation formation. Finally, two species stand out that would not be protected in anyarea, namely L. andinus and L. nigrocoeruleus.